COMPARATIVE ANTIOXIDANT ACTIVITIES OF CRUDE ETHANOLIC AND SAPONIN RICH BUTANOL EXTRACTS OF TRIBULUS TERRESTRIS FRUITS - S.HEMALATHA; RAJESWARI HARI (International Journal of Pharma and Bio Sciences, 2013)
A comparative free radical scavenging activity of ethanolic crude extract (EETT) and its saponin rich butanol fraction (SFTT) of Tribulus terrestris was investigated. The total antioxidant activity and the reducing capacity were also compared. The ethanolic crude extract and the saponin rich butanol fractions were prepared and its ability to scavenge free radicals such as nitric oxide, hydroxyl radical and hydrogen peroxide were investigated employing various established in-vitro systems. The total antioxidant activity was estimated using phosphomolybdenum method. The total reducing capacity was also estimated using potassium ferric cyanide method. The results revealed that the saponin rich butanol extract has notable quenching of nitric oxide, hydroxyl radical and hydrogen peroxide radicals when compared to the ethanolic crude extract of Tribulus terrestris. The SFTT at 1mg/ml showed maximum scavenging of nitric oxide (90.30%) hydroxyl ( 90.02%) and hydrogen peroxide ( 89.00%) against the scavenging of EETT which showed nitric (76.19%) hydroxyl (74.31%) and hydrogen peroxide (51.26%) radicals respectively at the same concentration. A linear correlation between these extracts and reducing power and total antioxidant activity were observed with SFTT showing pronounced activity than the EETT. The results of this study strongly indicate that the SFTT has more potent antioxidant activity than the crude EETT.